2023
DOI: 10.1101/2023.04.17.537087
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

mRNA Localization and Local Translation of the Microtubule Severing Enzyme, Fidgetin-Like 2, in Polarization, Migration and Outgrowth

Abstract: Cell motility requires strict spatiotemporal control of protein expression. During cell migration, mRNA localization and local translation in subcellular areas like the leading edge and protrusions are particularly advantageous for regulating the reorganization of the cytoskeleton. Fidgetin-Like 2 (FL2), a microtubule severing enzyme (MSE) that restricts migration and outgrowth, localizes to the leading edge of protrusions where it severs dynamic microtubules. FL2 is primarily expressed during development but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 71 publications
0
6
0
Order By: Relevance
“…Translational regulation is another area that has provided insight into why some MSEs are only expressed under certain conditions. Our lab has found that wild‐type levels of FL2 protein in many adult cells under static conditions is low (R. L. Birnbaum, 2023); however, FL2 protein expression locally increases at the cell edge after injury to a monolayer, which was shown to be mediated by local translation in cells on the wound periphery (R. Birnbaum et al, 2023; R. L. Birnbaum, 2023). FL2 mRNA similarly localized to the leading edge of cells, suggesting the involvement of local protein synthesis in response to the injury.…”
Section: Fidgetin Family Regulation: Who's Holding the Scissors?mentioning
confidence: 99%
See 4 more Smart Citations
“…Translational regulation is another area that has provided insight into why some MSEs are only expressed under certain conditions. Our lab has found that wild‐type levels of FL2 protein in many adult cells under static conditions is low (R. L. Birnbaum, 2023); however, FL2 protein expression locally increases at the cell edge after injury to a monolayer, which was shown to be mediated by local translation in cells on the wound periphery (R. Birnbaum et al, 2023; R. L. Birnbaum, 2023). FL2 mRNA similarly localized to the leading edge of cells, suggesting the involvement of local protein synthesis in response to the injury.…”
Section: Fidgetin Family Regulation: Who's Holding the Scissors?mentioning
confidence: 99%
“…Investigation into the RNA‐binding proteins (RBP) that mediated this mRNA localization suggests that the RBPs IMP1 and IMP2 are involved in this process. RBPs bind mRNAs to control their subcellular localization, local translation, and degradation, thereby tightly regulating their local and temporal expression (R. Birnbaum et al, 2023; R. L. Birnbaum, 2023).…”
Section: Fidgetin Family Regulation: Who's Holding the Scissors?mentioning
confidence: 99%
See 3 more Smart Citations